A computed tomography phantom study of foam earplugs: Uncommon but potentially hazardous foreign body ingestion in children. Issue 35 (August 2016) - Hsu, Li-Sheng; Yen, Ju-Bei; Wang, Shie-Shan; Liao, Chien-Lin
Abstract : Abstract: Ingestion of a foreign body is common among children. However, ingestion of foam earplugs (FEPs) has not been reported previously. A 7-month-old female infant presented with small bowel obstruction, which was finally proved to be a case of FEP ingestion. Computed tomography (CT) phantom study was performed to examine the imaging features of FEPs. We studied the following dry and fully wet FEPs, FEPs squeezed in pure water to varying degrees, and FEPs with different degrees of compression in the dry and wet states from day 0 to 6 and all scanned with a CT scanner. The density of a dry FEP is −843.5 ± 4.5 Hounsfield units (HU) and it increases to 0.76 ± 9.3 HU when fully wet. The densities of FEPs ranged from −844.2 to 1.0 HU with different water/air ratios, and some showed a heterogeneous geographic pattern. The densities of FEPs increase due to compression and gradual water absorption. FEPs can be potentially hazardous objects to children. Owing to the special foam structure of the FEP, it can mimic a fatty lesion if the density ranges from −100 to −50 HU; moreover, it can hide in the water if fully wet. However, it should not be mistaken as air, as the density of a dry FEP is −843.5 HU, and the contour can be observed if the window level is set appropriately. Because of its soft texture, the surgeon should be careful not to miss an FEP during the operation. Moreover, radiologists should be familiar with the CT features of FEPs so that they can be identified before surgery.